Ectopic Fetal Hepatic Tissue in the Placenta. (September 2019) - Stonko, David P.; Liang, Jiancong; Weeks, Amy G.; Redline, Raymond W.; Boyd, Theonia K.; Watkins, Jaclyn C.; Kovach, Alexandra E.
Abstract : When an unusual intraplacental lesion is identified during pathologic examination, it becomes of substantial import to determine whether it represents a normal structure, metastasis from the mother, or a primary benign tumor, including those secondary to abnormal embryologic development versus a primary malignant placental tumor. In this case report, we identified an incidental nest of intraplacental cells with nondiagnostic morphology and negative initial Glypican-3 stain in a healthy 35-wk gestation. This negative result prompted a broadening of the differential before ultimately determining this lesion was indeed ectopic liver with positive Arginase-1 and HepPar-1 staining. This may represent the mature hepatocyte phenotype within the lesional cells of this near-term birth, a dichotomy not previously discussed in the literature, which focuses on the fetal hepatocyte phenotype, also rarely seen. In this report, we summarize the previous literature regarding intraplacental ectopic liver, and we propose a sensitive approach to suspected ectopic liver of the placenta that may be sufficient to capture both the fetal and mature hepatocyte immunophenotypes. This approach may extend to other related pathologies including assessment of suspected intraumbilical hepatocytes.